Keidel family papers - Keidel, George C. (George Charles), 1868-1942.
Keidel family papers. Chiefly the papers of George C. Keidel, professor of romance languages at Johns Hopkins University and later an employee of the Library of Congress Copyright Office, including correspondence, annotations, and writings concerning his study of Aesop's Fables and other early works. Also includes letters (1861-1865) of Herman F. Keidel to his family in Maryland while serving with the 12th Virginia Cavalry Regiment at the battle of Antietam, Md., and as a prisoner at the Point Lookout Prison Camp for Confederates, Point Lookout, Md., and Fort Delaware, Del. Papers of Louis J. Keidel (also known as Ludwig) include bills, insurance policies, and birth and baptismal certificates. Also includes a biographical sketch of Christian Wilhelm Brauns, Hessian soldier in the American Revolution; and a scrapbook containing illustrations of birds and ornithological material that belonged to George C. Keidel's in-laws, the Jacob B. Garber family of Lancaster County, Pa.
Collection material in English, with French, German, and Latin.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Biographical sketch of Christian Wilhelm Brauns was formerly cataloged separately under the author, George C. Keidel, and housed in Miscellaneous Manuscripts collection.
Keywords: Brauns, Christian Wilhelm, -- 1757-1809.; Garber, Jacob B; Garber family; Keidel family; Confederate States of America. -- Army. -- Virginia Cavalry Regiment, 12th.; Johns Hopkins University -- Faculty; Library of Congress. -- Copyright Office -- Officials and employees; Point Lookout Prison Camp for Confederates; Aesop's fables; Antietam, Battle of, Md., 1862.; Birds -- Pictorial works; Ornithology; Prisoners of war -- Delaware -- Fort Delaware; Prisoners of war -- Maryland -- Point Lookout; Romance languages -- Study and teaching; Delaware -- History -- Civil War, 1861-1865.; Fort Delaware (Del.); Lancaster County (Pa.); Maryland -- History -- Civil War, 1861-1865.; Point Lookout (Md.) -- History; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; United States -- History -- Revolution, 1775-1783 -- Participation, German; Virginia -- History -- Civil War, 1861-1865.; Keidel, Herman F; Keidel, Louis J. -- 1834-